Why Should I? Avoid Fatty Foods - Dalton, Cindy Devine (Vero Beach, Fla. : Rourke Book Co., 2001)
Describes animal and vegetable fat, which foods contain these fats, diseases which occur from eating too much fat, and the importance of eating a balanced diet.
Includes bibliographical references (p. 24) and index.
Keywords: Fat -- Juvenile literature; Lipids in human nutrition -- Juvenile literature; Fat; Nutrition